2020
DOI: 10.1111/cge.13865
|View full text |Cite
|
Sign up to set email alerts
|

Cutis laxa: A comprehensive overview of clinical characteristics and pathophysiology

Abstract: Cutis laxa (CL) syndromes comprise a rare group of multisystem disorders that share loose redundant skin folds as hallmark clinical feature. CL results from impaired elastic fiber assembly and homeostasis, and the known underlying gene defects affect different extracellular matrix proteins, intracellular trafficking, or cellular metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 61 publications
1
39
0
Order By: Relevance
“… 14 , 28 Cutis laxa is a genetically variable disease characterized by defective elastin metabolism and abnormal elastic fibers, which contribute to inelastic, saggy skin that affects the whole body; some cases are inherited (via 3 possible modes of inheritance: autosomal dominant, autosomal recessive, or X-linked recessive) and others are acquired (ie, acquired cutis laxa). 14 , 29 , 30 To date, there are no specific treatments for cutis laxa; thus, a better understanding of the disruption of, and approaches to repairing, elastic fiber networks could potentially assist patients with this disease.…”
Section: Clinical Relevance Of Elastinmentioning
confidence: 99%
“… 14 , 28 Cutis laxa is a genetically variable disease characterized by defective elastin metabolism and abnormal elastic fibers, which contribute to inelastic, saggy skin that affects the whole body; some cases are inherited (via 3 possible modes of inheritance: autosomal dominant, autosomal recessive, or X-linked recessive) and others are acquired (ie, acquired cutis laxa). 14 , 29 , 30 To date, there are no specific treatments for cutis laxa; thus, a better understanding of the disruption of, and approaches to repairing, elastic fiber networks could potentially assist patients with this disease.…”
Section: Clinical Relevance Of Elastinmentioning
confidence: 99%
“…Acquired cutis laxa is a rare skin condition that is associated with prior inflammatory diseases that results in elastolysis [41,42]. However, recent reports showed that the presence of an underlying monoclonal gammopathy as a potential cause [43][44][45].…”
Section: Acquired Generalized Cutis Laxamentioning
confidence: 99%
“…In cases with ARCL1B, the clinical picture varies in severity from mild form associated with vascular abnormalities (aneurysms, stenosis, tortuosity) and craniofacial dysmorphism to severe fatal form associated with severe musculoskeletal deformities and prenatal mortality. [1][2][3] We are reporting a case of ARCL1B presented with cardiac tamponade secondary to impending rupture of a giant aneurysm of the ascending aorta and the aortic arch.…”
Section: Introductionmentioning
confidence: 99%